Answer:
x = 2, -2, -1/5
Step-by-step explanation:
g(x)= 5x^3+x^2-20x-4
g(x)= x^2(5x+1)-4(5x+1)
g(x)=(x^2-4)(5x+1)
g(x)=(x-2)(x+2)(5x+1)
x-2=0
x= 2
x+2=0
x= -2
5x+1=0
x= -1/5
I’m assuming what you’re asking here is how to *factor* this expression. For that, let’s rearrange the expression into a more familiar form:
-c^2-4c+21
From here, we’ll factor out a -1 so that we have:
-(c^2+4c-21)
Let’s focus on the quadratic expression inside the parentheses. To find our factors (c + x)(c + y), we’ll need to find two terms x and y that multiply together to make -21 and add together to make 4. It turns out that the numbers -3 and 7 work out perfectly for that purpose (-3 x 7 = -21 and 7 + (-3) = 4), so substituting them in for x and y, we have:
(c + (-3))(c + 7)
(c - 3)(c + 7)
And adding back on the negative from a few steps earlier:
-(c - 3)(c + 7)
Answer:
Vertex - (2,1)
minimum
Step-by-step explanation:
minimum y≥1